Do four or more antenatal care visits increase skilled birth attendant use and institutional delivery in Bangladesh? A propensity-score matched analysis - Bridget L. Ryan; Rohin J. Krishnan; Amanda Terry; Amardeep Thind (BMC, 2019)
Abstract Background With Bangladesh's adoption of the third Sustainable Development Goal to reduce maternal mortality, the impetus for Bangladesh to continue to improve uptake of maternal healthcare is strong. Methods Using a propensity-score matched analysis, the present study utilized data from the 2014 Bangladesh Demographic Health survey to examine the impact of four or more antenatal care visits on skilled birth attendant use and institutional delivery. Results The results revealed a significant and positive impact of four or more antenatal care visits on skilled birth attendant use and institutional delivery after matching treated and untreated mothers on included socio-demographic characteristics. Conclusions Implementation of policies to provide at least four antenatal care visits may serve as an effective strategy to increase SBA use and institutional delivery in Bangladesh, which could contribute to the reduction of maternal mortality.